2015
DOI: 10.1016/j.juro.2014.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Intracompartmental Pressure as a Predictor of Intratesticular Blood Flow: A Rat Model

Abstract: This is the first known study to characterize a stop flow pressure within the testicular parenchyma resulting from an increased intracompartmental pressure. Due to probe sensitivity limitations, color flow appears to provide the most precise mean pressure of occlusion of 52.17 mm Hg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Though local injection can bypass the blood-testis barrier and directly affect the testis, it is not a good treatment option in clinical practice. The potential risk of compartment syndrome by local injection has limited its clinical application [ 11 , 12 ]. In our previous study of I/R injury of the kidney, intravenous stem cells still conducted a great protective effect though they were blocked in the lung [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though local injection can bypass the blood-testis barrier and directly affect the testis, it is not a good treatment option in clinical practice. The potential risk of compartment syndrome by local injection has limited its clinical application [ 11 , 12 ]. In our previous study of I/R injury of the kidney, intravenous stem cells still conducted a great protective effect though they were blocked in the lung [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that MSCs transplanted by local injection into I/R injured testis played a protective effect on germ cells [ 10 ]. However, local injection of MSCs may aggravate the intracompartmental pressure of testis, resulting in an occlusion of the microvascular bed that feeds the testicular lobules [ 11 , 12 ]. On the other hand, intravenous injection might be an appropriate transplantation method for MSCs, which can avoid these risks.…”
Section: Introductionmentioning
confidence: 99%
“…4 Intraparenchymal monitoring of testicular pressures has also shown how complex the reperfusion process can be after detorsion and the development of a compartment syndrome. [4][5][6] This intraoperative method is invasive and technically complex, which makes it not accessible and not reproducible in each and every case. To date, there is no objective method to assess testicular reperfusion that can be used for intraoperative decision making.…”
Section: Introductionmentioning
confidence: 99%